Model Pembalikan Mitos Rangda - I Gusti Ayu Agung Mas Triadnyani (SUSASTRA: Jurnal Ilmu Susastra dan Budaya, 2017)
A myth of Rangda is just not a property of Balinese people. An image of Rangda as a destructive power has been long acknowledged through centuries.1 However, in the modern era there is a new image dealing with the powerful Rangda, and it provides a noble value to the myth. Rangda appears as a protector in the novel Janda dari Jirah. This article wants to show how the novel’s author creatively imposes the new image of Rangda. This phenomenon could hopefully stimulate many writers to suggest creative work in which the classical works would be themain resources. The conclusion is religious complexion of Buddhism which suggests a breakthrough against the old perspective which exclusively emphasized the concepts of Siwa. It can be said that novel Janda dari Jirah seems to offer a renewal by reversal as it is told by Riffaterre (1978).